Genome-wide identification, characterization, and functional analysis of the CHX, SOS, and RLK genes in Solanum lycopersicum under salt stress - Amaal Maghraby; Mohamed Alzalaty (Scientific Reports)
Abstract The cation/proton exchanger (CHX), salt overly sensitive (SOS), and receptor-like kinase (RLK) genes play significant roles in the response to salt stress in plants. This study is the first to identify the SOS gene in Solanum lycopersicum (tomato) through genome-wide analysis under salt stress conditions. Quantitative reverse transcription PCR (qRT-PCR) results indicated that the expression levels of CHX, SOS, and RLK genes were upregulated, with fold changes of 1.83, 1.49, and 1.55, respectively, after 12 h of exposure to salt stress. Genome-wide analysis revealed 21 CHX, 5 SOS, and 86 RLK genes in S. lycopersicum. CHX genes were found on chromosomes 2, 3, 4, 5, 6, 7, 8, 9, 11, and 12 of S. lycopersicum. SOS genes were found on chromosomes 1, 4, 6, and 10. RLK genes were found on all chromosomes of S. lycopersicum. The Ka/Ks ratios indicate that the CHX, SOS, and RLK genes have been primarily influenced by purifying selection. This suggests that these genes have faced strong environmental pressures throughout their evolution. Purifying selection typically results in a decrease in genetic diversity. The estimated duplication time for CHX paralogous gene pairs ranged from approximately 26.965 to 245.413 million years ago (Mya), while the duplication time for SOS paralogous gene pairs ranged from around 116.682 to 275.631 Mya. For RLK paralogous gene pairs, the duplication time varied from approximately 27.689 to 239.376 Mya. Synteny analysis of the CHX, SOS, and RLK genes demonstrated collinear relationships with orthologous genes in Arabidopsis thaliana, but no collinearity orthologous relationships in Oryza sativa (rice). Furthermore, the analysis revealed that there were 6 orthologous SlCHX genes, 2 orthologous SlSOS genes, and 44 orthologous SlRLK genes paired with those in A. thaliana. The results of the present study may help to elucidate the role of the CHX, SOS, and RLK genes in salt stress in S. lycopersicum.